A Sulfuryl Group Transfer Strategy to Selectively Prepare Sulfated Steroids and Isotopically Labelled Derivatives - Alshehri, Jaber A.; Gill, Daniel M.; Jones, Alan M. (Frontiers in Molecular Biosciences, 2021)
The treatment of common steroids estrone, estradiol, cortisol, and pregnenolone with tributylsulfoammonium betaine (TBSAB) provides a convenient chemoselective conversion of the steroids alcohol/phenol moiety to the corresponding steroidal organosulfate. An important feature of the disclosed methodology is the scalability of the reaction, and the isolation of the corresponding steroid sulfates as their biologically relevant sodium salts without the need for ion-exchange chromatography. The scope of the method was further explored in the estradiol and pregnanediol steroid systems with the bis-sulfated derivative. Ultimately, a method to install an isotopic label, deuterium (2H) combined with estrone sulfation is a valuable tool for its mass-spectrometry quantification in biological studies.